HEALTH NUTRITION EDUCATION AND STRENGTHENING INDONESIAN CULTURE AMONG INDONESIAN MIGRANT WORKERS CHILDREN IN MALAYSIA - Rahmaddiansyah, Refa; Azizah, Aghasi Yanda Wafa; Abdurrahman, Adisa Muhammad; Muftiana, Sintya Nur; Haq, Addienul; Riswanti, Laila Wulan; Jalilah, Thurfah Hashifah; Masthurina, Ulfa; Hrp, Maritza Briliani Namora; Tambunan, Mega Intan; Pelani, Achmad Aziz; Noviar, Tita Falisha; Abdurrahman, Thariq; Azizah, Siti Nur (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2024)
This service aims to improve children's understanding of balanced nutrition and promote their cultural awareness. The methods used in this program include integrated learning activities that focus on health education and cultural awareness. The materials used are from the "Isi Piringku" nutrition guide, which teaches children about the importance of a healthy diet. In addition, the program also organizes interactive sessions on local foods and iconic Indonesian landmarks to foster cultural pride. A total of 41 children participated in this activity, which included puzzles, flashcards, and a nutritional assessment to evaluate their dietary habits. In addition, traditional dances were also taught to introduce Indonesian culture and strengthen the cultural identity of migrant children. The results of the activities showed an increase in children's understanding of balanced nutrition and Indonesian culture, as well as the importance of pride in their heritage. The program also succeeded in introducing a more collaborative learning approach, involving parents in the child's education process. However, further research is needed on the role of parental involvement in supporting the success of this program. Overall, the "Anak CERIA" program is in line with the 2030 Sustainable Development Goals, especially in improving the education and health of Indonesian migrant children, as well as strengthening their cultural awareness. This initiative is expected to inspire similar programs in the future. Keywords: SDGs, PMI Children, Health Education, Cultural Awareness, Community Empowerment